The validity and reliability of a sample of 10 Wattbike cycle ergometers. Issue 14 (18th July 2017) - Wainwright, Barney; Cooke, Carlton Brian; O'Hara, John Paul
ABSTRACT: The purpose of the study was to assess the validity and inter-bike reliability of 10 Wattbike cycle ergometers, and to assess the test–retest reliability of one Wattbike. Power outputs from 100 to 1000 W were applied using a motorised calibration rig (LODE) at cadences of 70, 90, 110 and 130 rev · min −1, which created nineteen different intensities for comparison. Significant relationships ( P  < 0.01, r 2  = 0.99) were found between each of the Wattbikes and the LODE. Each Wattbike was found to be valid and reliable and had good inter-bike agreement. Within-bike mean differences ranged from 0.0 W to 8.1 W at 300 W and 3.3 W to 19.3 W at 600 W. When taking into account the manufacturers stated measurement error for the LODE (2%), the mean differences were less than 2%. Comparisons between Wattbikes at each of the nineteen intensities gave differences from 0.6 to 25.5 W at intensities of 152 W and 983 W, respectively. There was no significant difference ( P  > 0.05) between the measures of power recorded in the test–retest condition. The data suggest that the Wattbike is an accurate and reliable tool for training and performance assessments, with data between Wattbikes being able to be used interchangeably.